Analysis of Communication Barriers to Distance Education: A Review Study - Dabaj, Fahme; Yetkin, Aysegul (Online Journal Communication & Media Technologies-Ojcmt, 2011)
Now that the technology is changing fast and due to the multitude of people demands and conditions, traditional educational systems and institutions have to provide additional educational alternatives. There are some educational establishments contributing to these conditions and demands by developing and offering distance education programs. In such programs, teachers and the students do not establish a face to face communication thus creating difficulties and are separated by physical distance and time. As a result alternate media sources are used to deal with these difficulties. That is to say, different delivery systems such as computer mediated communication systems, video tapes, printed material, cassettes and instructional television are used to deliver instructions from tutor to students. Moreover, the universities have the advantage of using World Wide Web to deliver the instruction to nearly any node in the world, regardless of the physical distance and time because of the developments in the Internet and the global network systems, Almost all institutions which are offering distance education should try and find the most effective program and make sure that it is a sufficient replacement for face-to-face education. Its effectiveness of course is dependent on how interactive the process is and how it overcomes the communication barriers among the members involved. Communication barriers, on the other hand, as in any communication process, also exist in distance education because of such reasons as the physical distance between members, the difficulties of dealing with new media, having time constraints and restrictions, background knowledge of distance education, incompetence in skills of using technology, and the interactivity level of the process. Put all together, effective distance education process becomes almost impossible. The levels of these barriers are different in different institutions or in different programs and in different delivery systems used.